Sensitization to PR-10 proteins is indicative of distinctive sensitization patterns in adults with a suspected food allergy. Issue 1 (December 2017) - Blankestijn, Mark; Knulst, André; Knol, Edward; Le, Thuy-My; Rockmann, Heike; Otten, Henny; Klemans, Rob
Abstract Background The extent of co-sensitization within and between food protein families in an adult population is largely unknown. This study aimed to identify the most frequently recognized components in the PR-10 and storage protein family, as well as patterns in (co-)sensitization, in a birch-endemic area. Methods Results of ImmunoCAP ISAC, performed during routine care in Dutch adult outpatients suspected of food allergy, were collected. Results A total of 305 patients were selected, aged 16–79 years (median 32 years). Sensitization to one or more PR-10 proteins was most frequent (74% of all subjects), followed by 35% to storage protein and 15% to nsLTPs. Within the PR-10 family, subjects were most often sensitized to Bet v 1 (73% of 305), Cor a 1.04 (72%) and Mal d 1 (68%). Sensitization to PR-10s from soy, celery and kiwi occurred distinctively less often (< 55% of Bet v 1 sensitized subjects) compared to other food PR-10s (all > 70%). Subjects sensitized to these 'less common PR-10 proteins' were sensitized to more food and inhalant components on the ISAC, compared to subjects sensitized to 'common PR-10 proteins' (median 22 vs 13 out of 112, p  < 0.0001). Seven subjects demonstrated sensitization to food PR-10 proteins, without concomitant sensitization to pollen PR-10s. Within the storage proteins, sensitization to multiple peanut allergens was most common (on average 3 out of 4). Conclusions Sensitization to PR-10 food proteins could occur without concomitant sensitization to common PR-10 from pollen in a subset of subjects. Less commonly recognized PR-10 proteins appear to be an indication of polysensitization.